Impact on green design-based RMG factories of Bangladesh in 21st century from the perspective of Dekko Accessories Limited - Safwan, H.M. (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.